1986
DOI: 10.1093/carcin/7.8.1309
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and hepatocarcinogenesis in rats fed a choline-devoid diet

Abstract: Groups of male Fischer-344 rats were fed either a choline-supplemented or a choline-devoid (CD) diet, for up to 14 months. In rats fed the CD diet, hepatic lesions developed and progressed through two distinct stages, the first characterized by severe steatosis and an increase in cell turnover and the second by gradual clearance of the deposited fat, fibrosis and parenchymal nodularity. Large hepatocellular carcinomas were found in rats killed at 14 months. DNA was purified from the livers of all groups of rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
6

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 0 publications
4
44
1
6
Order By: Relevance
“…Dietary choline deficiency not only depletes choline and choline metabolites in rats, but also decreases S-adenosylmethionine concentrations (117,164), with resulting hypomethylation of DNA (74,134). DNA methylation occurs at cytosine bases that are followed by a guanosine (CpG sites) (52) and influences many cellular events, including gene transcription, genomic imprinting, and genomic stability (60,64,105).…”
Section: Choline and Brain Development In Uteromentioning
confidence: 99%
“…Dietary choline deficiency not only depletes choline and choline metabolites in rats, but also decreases S-adenosylmethionine concentrations (117,164), with resulting hypomethylation of DNA (74,134). DNA methylation occurs at cytosine bases that are followed by a guanosine (CpG sites) (52) and influences many cellular events, including gene transcription, genomic imprinting, and genomic stability (60,64,105).…”
Section: Choline and Brain Development In Uteromentioning
confidence: 99%
“…During choline deficiency, hepatic SAM concentrations are decreased by as much as 50% [45][46][47][48]. Animals fed diets deficient in methyl donors (choline and methionine) have hypomethylated DNA [49][50][51]. These deficiencies have been shown to cause both global [52] and gene-specific hypomethylation [53].…”
Section: Animal Studiesmentioning
confidence: 99%
“…Many studies have demonstrated that feeding a choline-devoid diet to experimental animals is carcinogenic [20][21][22][23][24][25][26][27][28][29][30]. There are several mechanisms which have been suggested to explain this effect: increased cell death, increased cell proliferation, decreased DNA methylation, and increased lipid peroxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Methylation of DNA is important for the regulation of gene expression [34]. It has been suggested that the under-methylation of DNA (decreased 5-methylcytosine content in nuclear DNA), observed during choline deficiency, is responsible for carcinogenesis [26]. Another proposed mechanism is based upon the observation of increased lipid peroxidation in hepatic nuclei isolated from CD animals [35].…”
Section: Resultsmentioning
confidence: 99%